(untitled) (LEARNing Landscapes, 2014)
This paper is an autobiographical narrative inquiry into lived experiences in home and school places. Drawing on Huber, Murphy, and Clandinin’s (2011) reconceptualization of curriculum making as occurring in two worlds (Lugones, 1987), the author explores the tensions that existed between her early familial curriculum-making world and her school curriculum-making worlds. Inquiring into the embodied tensions she carries, the author recognizes how she privileges school curriculum making over familial curriculum making in schools, and wonders of the costs to the children she teaches, as well to herself in doing so.